Management of pregnancy-associated breast cancer: A case series and review of multidisciplinary treatment approaches - Fania Pancar Fadilla; Febriani Febriani (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Pregnancy-associated breast cancer (PABC) refers to breast cancer identified either during gestation or within the first year following childbirth. Managing PABC presents distinct clinical complexities, as it necessitates a careful balance between effective maternal therapy and ensuring fetal safety. Purpose: This case series seeks to detail the clinical characteristics, diagnostic procedures, and treatment approaches utilized in managing PABC. Method: We report multiple cases involving pregnant women diagnosed with breast cancer at different stages of gestation. Information was gathered regarding clinical presentation, gestational age at diagnosis, types and timing of treatment interventions (such as surgery and chemotherapy), as well as maternal and fetal outcomes. Results: The cases underscore the critical role of early detection and a multidisciplinary team approach. Treatment strategies were tailored according to gestational age and cancer stage. Chemotherapy was generally administered without significant complications during the second and third trimesters, and surgical procedures were planned to prioritize both maternal and fetal health. Conclusion: Effective management of PABC demands close coordination between oncology and obstetrics teams. With appropriate planning and individualized care, it is possible to treat breast cancer during pregnancy without substantially endangering fetal health.